ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIC DI RAHARJO MOTOR, JEPARA - Kurniawan, Tomi; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2013)
This research was based a decrease in sales of Suzuki Matic motorcycles in the period 2011-2012 in Raharjo Motor. Raharjo Motor has been doing marketing efforts to attract consumers. This study aimed to determine the effect of three variables, they are product quality, service quality and location to purchasing decision at Raharjo Motor.The research was conducted at Raharjo Motor. In this research, the data was collected by tools such as questionnaires given to 100 respondents, in order to determine respondent’s responses to each variable. The analysis used in this research includes validity test, reliability test, classic assumption test (normality test, multicolinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing via t test and F test, and analysis of coefficient of determination (R2). From the results of regression analysis can be known that variables of product quality, service quality, and location have positive effect on purchasing decisions when buying at Raharjo Motor in which product quality is the most influential variable on purchasing decisions, followed by service quality and, location.